Desain dan Uji Coba Media Pembelajaran Alat Peraga Penjernihan Air Sederhana Berorientasi Green Chemistry Pada Materi Koloid di SMA Negeri 1 Pekanbaru - neti afrianis; dwi safitri anggreani (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2020)
This research was instigated by the unavailability of the instructional media implementing green Chemistry concept and the limitation of laboratory facilities at State Senior High School 1 Pekanbaru.  It aimed at knowing the validity and practicality levels of Green Chemistry oriented Simple Water Purifier prop instructional media on Colloid lesson, the guidebook of constructing and using props.  It was Research and Development (R&D) with 4D development model.  The technique of collecting the data was questionnaire.  Instruments of collecting the data were validity test questionnaire, practicality test questionnaire, and student response questionnaire.  The assessment of the prop and guidebook by the experts of material showed the percentages continuously 93.33% and 90%.  The assessment of the prop and guidebook by the experts of media showed the percentages continuously 80.95% and 83.33%.  The practicality assessment of the prop and guidebook by the teachers showed the percentages continuously 94.25% and 98.33%.  The practicality assessment by the students showed the percentage 90.25%.